Feasibility study: Assessing the influence of macronutrient intakes on preterm body composition, using air displacement plethysmography. (14th April 2015) - McLeod, Gemma; Simmer, Karen; Sherriff, Jill; Nathan, Elizabeth; Geddes, Donna; Hartmann, Peter
<x xml:space="preserve">Abstract</x> Aim Preterm nutrition guidelines target nutrient accretion and growth at intrauterine rates, yet at term equivalent age, the phenotype of the preterm infant differs from that of term infants. Monitoring early changes in preterm body composition (BC) in response to macronutrient intakes may facilitate our understanding of how best to meet preterm nutrition and growth targets. Method Macronutrient intakes based on milk analysis were calculated from birth for infants born <33 weeks gestation. BC was measured in the PEA POD when infants were thermodynamically stable, free of intravenous lines and independent of respiratory support. Subsequent BC measurements were taken at least fortnightly until term age. Regression analysis was used to assess macronutrient influences on changes in BC. Results Median (range) gestation and birthweight of preterm infants (n = 27) were 29 (25–32) weeks and 1395 (560–2148) g, respectively. The youngest corrected gestational and postnatal ages that infants qualified for a PEA POD measurement were 31.86 and 1.43 weeks, respectively. Fat and total energy intakes were positively associated with increasing fat mass. Protein (with carbohydrate) intake was positively associated with increasing fat‐free mass. Conclusion Preterm infants can be measured in the PEA POD as early as 31 weeks corrected gestational age and the method appears sufficiently sensitive to detect influences of macronutrient intake on changes in BC.